Gamification Strategy in Duolingo Application on Student Learning Motivation - Repido Yogi Ganesha (Teaching and General Education Studies, 2026)
This research is based on the increasing utilization of learning applications based on gamification, especially Duolingo, which is believed to be able to strengthen the learning motivation of students in learning a foreign language. This research aims to analyze the gamification strategy that is applied in the application and its influence on the learning drive of students at the university level. The method that is used is qualitative analysis through the study of empirical findings data, application usage patterns, and student learning experience that shows a response to gamification elements such as points, levels, feedback, and daily challenges. The research results show that these features play a role in building consistent learning involvement, increasing a sense of competence, and growing interest towards the language material. Analysis also shows that Duolingo helps students maintain a study routine, reduce boredom, and provide a more adaptive learning experience. Implication: This research emphasizes the importance of gamification integration in the development of digital learning media, as well as providing a foundation for educators and institutions to design more creative learning strategies to increase the motivation and quality of the student learning process.